Why Guarantee Employment? Evidence from a Large Indian Public-Works Program - Laura Zimmermann (Global Labor Organization (GLO), 2020)
Most countries around the world implement some form of a safety net program for poor households. A widespread concern is that such programs crowd out private-sector jobs. But they could also improve workers' welfare by allowing them to take on more risk, for example through self-employment. This paper analyzes the employment impacts of the world's largest public-works program using a novel regression-discontinuity design. The analysis exploits detailed institutional information to describe the allocation formula of the program and to construct a benefit calculator that predicts early and late treatment of districts. The results show that there is little evidence of a crowding out of private-sector jobs. Instead, the scheme functions as a safety net after a bad rainfall shock. Male workers also take on more risk by moving into family employment. This self-revealed preference for a different type of job suggests other potential benefits of safety net programs which so far have received little attention in the literature.
Keywords: H53; H75; I38; J22; J38; 330; public-works program; anti-poverty program; National Rural Employment Guarantee Scheme; NREGA; NREGS; India; regression discontinuity design; safety net; crowding out; risk coping; risk mitigation; insurance